Navajo Textiles : The Crane Collection at the Denver Museum of Nature and Science - Teller Pete, Lynda; Begay, D. Y., 1953-; Stiver, Louise; Webster, Laurie D., 1952- (Book collections on Project MUSE., 2017)
"An account of the historical context of Navajo weavings in the Crane Collection at the Denver Museum of Nature and Science--one of the largest collections in the world. Anthropologists and indigenous artists explore the Navajo rug trade in mid-nineteenth century and changes in Navajo textile market"--Provided by publisher.